Diskresi Kepolisian Dalam Penanganan Konflik Sosial : Kedudukan Peraturan Internal Kepolisian Dalam Penanganan Konflik Di Dalam Peraturan Perundang-undangan - Zulfa, Eva; Praptadina, Sri B (UI Scholars Hub, 2016)
The use of discretion as a means of handling and settlement of a dispute society, let alone carried out by law enforcement is essentially a matter of policy as authorized by law to officials. How discretion possessed by the police in handling conflicts in society. In reality discretion in many forms. One is through edicts Chief of Indonesian Police Central Sulawesi number NAK / 04 / I / 2013 on the prohibition of carrying weapons and other dangerous objects. Regional Leadership kemuadian issued edicts Chief of Indonesian Police Central Sulawesi number NAK / 04 / I / 2013 on the prohibition of carrying weapons and other dangerous objects It is issued in order to dampen the unrest in the county Sigi year 2013. It is interesting to examine notch regulations made by the police in handling conflict if the associated discretion possessed by the police